Pengembangan instrumen pengukuran prokrastinasi akademik pada siswa sekolah menengah pertama - Rachel Imanuela; Nyoman Dantes; Kadek Ari Dwiarwati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to identify and describe (1) the content validity of the instrument for measuring academic procrastination in junior high school students (2) the empirical validity of the instrument for measuring academic procrastination in junior high school students (3) the reliability of the instrument for measuring academic procrastination in junior high school students. This research is a development research (R&D). The procedure for developing this research uses ten steps in the development of the djemari mardapi instrument. Data was collected through observation and distributing questionnaires. Furthermore, the data were analyzed using the content validity test with the Lawshe formula, empirical validity test with the internal grain consistency formula (Product Moment), and reliability test with the formula (Alpha Cronbach). The results of the data analysis, based on the results of the internal empirical test for the consistency of the instrument items for measuring academic procrastination in students, obtained the results rxy (hit) > rxy (tab), indicating that overall the items were declared valid. While the results of the reliability test of the instrument for measuring academic procrastination in students amounted to 0.889 included in the results of the classification "Very High".